Diagnostic value of superb microvascular imaging and color doppler for thyroid nodules: A meta-analysis - Luo, Haorou; Yin, Lixue (Frontiers in Oncology, 2023)
Objective Superb micro-vascular imaging (SMI) is a new noninvasive modality for the diagnosis of thyroid nodules. However, the performance of SMI in differentiating malignant and benign thyroid nodules has not been systematically evaluated. This meta-analysis was performed to assess the accuracy of SMI in diagnosing thyroid nodules. Methods PubMed, Cochrane Library, Embase, Web of Science, Sinomed, Scopus were searched. We recorded the characteristics of the included studies and assessed the quality of each study using the QUADAS-2 tool. The pooled sensitivity, specificity, positive likelihood ratio (LR), negative LR, diagnostic odds ratio (DOR), and area under the curve (AUC) were calculated. We also evaluated the publication bias. Results This meta-analysis included 10 studies with a total of 1083 thyroid nodules. The pooled the sensitivity, specificity, and positive and negative LR were 0.84, 0.86, 6.2, and 0.18, respectively. The DOR and AUC were 33 and 0.91, respectively. Heterogeneity existed between the included studies. No significant publication bias was observed. Conclusion Compared with CDFI, Superb micro-vascular imaging (SMI) has higher diagnostic sensitivity and specificity, better diagnostic efficiency, and could be used to diagnose benign and malignant nodules in the display of blood flow distribution capabilities of thyroid nodules; at the same time, Fagan plot showed that the SMI technique had a good clinical application value, and it could supplement the deficiencies of color Doppler imaging in the diagnosis of thyroid nodules.